The Influence of Tourism Industry and Tourism Supply Chain on Tourism Performance - Sri Mulyani (Shirkah: Journal of Economics and Business, 2024)
This study explores the influence of stakeholders in the tourism industry in improving the tourism supply chain and tourism performance. This research employs a quantitative method to explore the pivotal role of stakeholders in Central Kalimantan's tourism industry, encompassing academicians and tourism industry professionals. Utilizing a structured questionnaire, 117 participants were selected through proportional stratified sampling. Data analysis employed a structural equation model (SEM). The study's results reveal a statistically significant and positive influence of stakeholders on both the tourism supply chain and tourism performance. Furthermore, it highlights the reciprocal influence of tourism supply chains on tourism performance. This research offers valuable insights for future investigations and informs strategies to boost Indonesia's tourism sector.